2015
DOI: 10.1155/2015/580582
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pr, Sm, and Tb Doping on the Morphology, Crystallite Size, and N2O Decomposition Activity of Co3O4 Nanorods

Abstract: Cobalt(II,III) oxide, Co3O4, is a promising catalyst for nitrous oxide direct decomposition. In this paper we report effect of doping with some rare earth (RE) elements (Pr, Sm, and Tb) on the morphology and crystallite size of Co3O4nanorods. The various precursors (RE/Co oxalates) were prepared via the microwave assisted method and subsequent calcination. The decomposition pathway of these precursors was followed using thermogravimetric analysis (TGA). Based on thermal analysis results, Pr-, Sm-, and Tb-doped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 33 publications
2
14
0
Order By: Relevance
“…Two other peaks can be observed at ~1485 cm −1 and ~1361 cm −1 , which are related to the metal carbonate structures [7,30]. The higher intensities of these two absorptions in the case of the RE-containing samples could be related to their high ability to form surface carbonate structures [21,22]. Inspection of Figure 3 reveals the absence of any peaks due to oxalate anion, suggesting complete decomposition of the precursors, which is in agreement with the XRD findings.…”
Section: Introductionsupporting
confidence: 84%
See 4 more Smart Citations
“…Two other peaks can be observed at ~1485 cm −1 and ~1361 cm −1 , which are related to the metal carbonate structures [7,30]. The higher intensities of these two absorptions in the case of the RE-containing samples could be related to their high ability to form surface carbonate structures [21,22]. Inspection of Figure 3 reveals the absence of any peaks due to oxalate anion, suggesting complete decomposition of the precursors, which is in agreement with the XRD findings.…”
Section: Introductionsupporting
confidence: 84%
“…This picture suggests a significant textural change of bare NiO upon the incorporation of RE-oxides. In this context, we reported that the incorporation of various RE-oxides into CuO and Co3O4 results in a noticeable decrease in their particles sizes [21,22,31]. Concurrently, Xue et al [10] reported a decrease in the Co3O4 SEM-estimated particles size after the addition of 5% of CeO2.…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations